Laboratory guide in zoology - Atienza, Rosario F. (Manila UST Printing Office, 1990)
A laboratory manual which aims to guide students in their exercises and experiments in Zoology. With detailed intructions and illustrations in black and white.
Mimeographed.
Keywords: Zoology -- Laboratory manuals